2016
DOI: 10.1021/acs.est.6b03270
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Products from Heterogeneous Oxidation of Squalene with Ozone

Abstract: Motivated by the importance of the heterogeneous chemistry of squalene contained within skin oil to indoor air chemistry, the surface reaction of squalene with gas-phase ozone has been investigated. Using direct analysis in real time mass spectrometry (DART-MS) to monitor squalene, the reactive uptake coefficients were determined to be (4.3 ± 2.2) × 10 and (4.0 ± 2.2) × 10 for ozone mixing ratios (MR) of 50 and 25 ppb, respectively, on squalene films deposited on glass surfaces. At an MR of 25 ppb, the lifetim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(177 citation statements)
references
References 53 publications
9
158
1
Order By: Relevance
“…Squalene contains 6 C=C bonds so it is highly reactive. Zhou et al 50 found that levulinic acid, succinic acid, and 4-oxobutanoic are the major condensed-phase products from heterogeneous ozonolysis of squalene. These acids can partition into the gas phase and were identified in the gas phase during this study, with their indoor concentration substantially higher than outdoors (Table S1).…”
Section: Concentration Of Indoor Andmentioning
confidence: 99%
“…Squalene contains 6 C=C bonds so it is highly reactive. Zhou et al 50 found that levulinic acid, succinic acid, and 4-oxobutanoic are the major condensed-phase products from heterogeneous ozonolysis of squalene. These acids can partition into the gas phase and were identified in the gas phase during this study, with their indoor concentration substantially higher than outdoors (Table S1).…”
Section: Concentration Of Indoor Andmentioning
confidence: 99%
“…In addition to the volatile products, the ozonolysis of squalene also generates a number of long-chained polyunsaturated aldehydes and carboxylic acids such as C27-pentaenal, C22-tetraenal, C17-trienal, C27-pentaenoic acid, C22-tetraenoic acid, C17-trienoic acid, that remain bound to the surface. 13 Other studies looked at ozone removal and product formation on clothes, 20 human hair 8 , pieces of clothes soaked with methanol extracts of human skin lipids, 21 on the heterogeneous mechanism of squalene/ozone reaction, 22 and on modeling of the processes with relevance to indoor environments. 18 The human surface has been shown to be very effective at removing ozone.…”
Section: Introductionmentioning
confidence: 99%
“…Proton transfer reaction mass spectrometer (PTR-MS) was used, for example, in the above-mentioned simulated aircraft cabin 11,12 and office experiments. 13 Other studies looked at ozone removal and product formation on clothes, 20 human hair 8 , pieces of clothes soaked with methanol extracts of human skin lipids, 21 on the heterogeneous mechanism of squalene/ozone reaction, 22 and on modeling of the processes with relevance to indoor environments. 18,19 Building ventilation is used to control the thermal environment and the concentrations of indoor air pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…When indoors, humans are exposed not only to ozone, but also to products of ozone‐initiated chemistry . Some of these products (eg, hydroxyl radicals, hydrogen peroxide, organic peroxides, formaldehyde, dicarbonyls, secondary organic aerosols) potentially contribute to the total mortality associated with long‐term exposure to ozone as evaluated using measured or modeled outdoor ozone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…50 When indoors, humans are exposed not only to ozone, but also to products of ozone-initiated chemistry. 20,23,36,[51][52][53][54][55][56][57][58][59][60][61][62][63][64] Some of these products (eg, hydroxyl radicals, hydrogen peroxide, organic peroxides, formaldehyde, dicarbonyls, secondary organic aerosols) potentially contribute to the total mortality associated with long-term exposure to ozone as evaluated using measured or modeled outdoor ozone concentrations. Indeed, some of the same products generated when ozone is inhaled are generated indoors and subsequently inhaled (albeit at much lower "intake ratios").…”
Section: Exposure To Indoor Ozone and Its Oxidation Productsmentioning
confidence: 99%